1984
DOI: 10.1056/nejm198408023110501
|View full text |Cite
|
Sign up to set email alerts
|

Bone Mineral Content of Amenorrheic and Eumenorrheic Athletes

Abstract: This study was designed to determine whether the hypoestrogenic status of 14 amenorrheic athletes was associated with a decrease in regional bone mass relative to that of 14 of their eumenorrheic peers. The two groups of athletes were matched for age, height, weight, sport, and training regimens. Bone mass was measured by dual-photon and single-photon absorptiometry at the lumbar vertebrae (L1 to L4) and at two sites on the radius. Vertebral mineral density was significantly lower in the amenorrheic group (mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
148
3
3

Year Published

1986
1986
2003
2003

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 885 publications
(162 citation statements)
references
References 18 publications
8
148
3
3
Order By: Relevance
“…Indeed, exercise can facilitate statural growth by stimulating growth hormone synthesis. In young female athletes, undertaking very intense aerobic exercise, oligomenorrhoea, amenorrhea, bone loss and stress fractures have been observed [31][32][33] . Approximately half of competitive female athletes experience oligomenorrhea or amenorrhea, compared to 5% in the general population.…”
Section: Can Excess or Wrong Exercise Be Dangerous For Bone?mentioning
confidence: 99%
“…Indeed, exercise can facilitate statural growth by stimulating growth hormone synthesis. In young female athletes, undertaking very intense aerobic exercise, oligomenorrhoea, amenorrhea, bone loss and stress fractures have been observed [31][32][33] . Approximately half of competitive female athletes experience oligomenorrhea or amenorrhea, compared to 5% in the general population.…”
Section: Can Excess or Wrong Exercise Be Dangerous For Bone?mentioning
confidence: 99%
“…It is estimated that at least 50% of competitive female athletes experience oligomenorrhoea or amenorrhoea compared with 5 % in the normal population (Carbon, 1992). Despite their high levels of activity, these women can lose bone, particularly in the lumbar spine (Drinkwater et al 1984;Rutherford, 1993). A low bone density may put the athlete at increased risk of stress fractures in the short term (Myburgh et al 1990) and osteoporosis later in life.…”
Section: The 'Dangers' Of Exercisementioning
confidence: 99%
“…The third point of interest was that these authors documented two runners below the fracture threshold, a finding similar to that reported by Drinkwater et a1. (5).…”
Section: Review Of Literaturementioning
confidence: 99%
“…(5). Bone density was measured in the distal radius and lumbar vertebrae (L1 -L4) of 28 female athletes.…”
Section: Review Of Literaturementioning
confidence: 99%